Life cycle assessment of swine production in Brazil: a comparison of four manure management systems. (15th January 2015) - Cherubini, Edivan; Zanghelini, Guilherme Marcelo; Alvarenga, Rodrigo Augusto Freitas; Franco, Davide; Soares, Sebastião Roberto
Abstract: Population growth and the consequent increase in food demand will certainly intensify the threat to the environment. Brazil, the fourth largest producer and exporter of swine meat, has an important role to ensure the fulfillment of the goals of food security and climate change mitigation. Therefore, the aim of this study was to evaluate the environmental impact of swine production in Brazil based on life cycle assessment, comparing four manure management systems: liquid manure storage in slurry tanks; the biodigestor by flare; the biodigestor for energy purposes; and composting. Additionally, we performed a Monte Carlo simulation to evaluate the uncertainty due to different emissions factors to estimate nitrogen-related emissions from the manure-handling stage. The functional unit considered was 1000 kg of swine carcass in the equalization chamber for cutting or further distribution. The results indicated an environmental profile of swine production in Brazil of 3503.29 kg of CO2 eq. for climate change, 76.13 kg of SO2 eq. for terrestrial acidification, 2.15 kg of P eq. for freshwater eutrophication, 12.33 kg of N eq. for marine eutrophication, 21, 521.12 MJ for cumulative energy demand, 1.63 kg of 1.4-DB eq. for terrestrial ecotoxicity, 1706.26 BDP for biodiversity damage potential and 14.99 m² for natural land transformation. Feed production had a significant contribution with a range of 17.6–99.5% for all environmental impact categories. Deforestation represented 9.5 and 31.3% of the total impacts for cumulative energy demand and climate change, respectively. Therefore, avoiding the use of grain from deforested areas can significantly decrease the impacts for these impact categories. Regarding the uncertainty analysis, we observed greater variations for terrestrial acidification in slurry tanks, biodigestor by flare and for energy purposes, while for the case of composting, major uncertainties were observed for climate change. For manure management systems, efforts should be made to reduce the emissions of methane in the storage and ammonia in the field application. In this sense, the comparative life cycle assessment indicated that the biodigestor for energy purposes had the best environmental performance for almost all the environmental impacts, mainly due to the biogas capture and the potential of energy saves. Nevertheless, if the goal is to decrease the impacts for terrestrial acidification and marine eutrophication, the slurry tanks is the most preferable scenario compared to all alternative options. Highlights: We compared four manure management systems of swine production in Brazil. We performed a Monte Carlo analysis for N-related emissions from the manure-handling. Feed production is the main source for the environmental impacts. Overall, the biodigestor for energy purposes had the best environmental performance. Monte Carlo simulation indicated great uncertainties for the N2 O emissions.